Effect of appendicectomy on colonic inflammation and neoplasia in experimental ulcerative colitis. Issue 11 (8th August 2016) - Harnoy, Y.; Bouhnik, Y.; Gault, N.; Maggiori, L.; Sulpice, L.; Cazals‐Hatem, D.; Boudjema, K.; Panis, Y.; Ogier‐Denis, E.; Treton, X.
Abstract: Background: Ulcerative colitis (UC) promotes cancer, and can be ameliorated by early appendicectomy for appendicitis. The aim of the study was to explore the effect of appendicectomy on colitis and colonic neoplasia in an animal model of colitis and a cohort of patients with UC. Methods: Five‐week old IL10/Nox1 DKO mice with nascent colitis and 8‐week‐old IL10/Nox1 DKO mice with established colitis underwent appendicectomy (for experimental appendicitis or no appendicitis) or sham laparotomy. The severity and extent of colitis was assessed by histopathological examination, and a clinical disease activity score was given. From a cohort of consecutive patients with UC who underwent colectomy, the prevalence of appendicectomy and pathological findings were collected from two institutional databases. Results: Appendicectomy for appendicitis ameliorated experimental colitis in the mice; the effect was more pronounced in the 5‐week‐old animals. Appendicectomy in the no‐appendicitis group was associated with an increased rate of colonic high‐grade dysplasia (HGD) or cancer compared with rates in sham and appendicitis groups (13 of 20 versus 0 of 20 and 0 of 20 respectively; P < 0·001). Fifteen of 232 patients who underwent colectomy for UC had previously had an appendicectomy, and nine of these had colonic cancer or HGD. Thirty (13·8 per cent) of 217 patients with the appendix in situ had colonic neoplastic lesions. Multivariable analysis showed that previous appendicectomy was associated with colorectal neoplasia (odds ratio 16·88, 95 per cent c.i. 3·32 to 112·69). Conclusion: Appendicectomy for experimental appendicitis ameliorated colitis. The risk of colorectal neoplasia appeared to increase following appendicectomy without induced appendicitis in a mouse model of colitis, and in patients with UC who had undergone appendicectomy. Surgical relevance Appendicectomy for appendicitis protects against UC. In this murine model of colitis, appendicectomy for experimental appendicitis protected against colitis, but appendicectomy without appendicitis promoted colorectal carcinogenesis. In patients with ulcerative colitis who underwent colectomy, absence of the appendix (proof of previous appendicectomy) in the resection specimen was independently associated with colorectal neoplasia. Although patients with UC and a history of appendicectomy represent a small subset, they may need closer monitoring for colorectal neoplasia. Abstract : Appendicectomy reduces inflammation, increases risk for cancer